Peningkatan Kemampuan Membaca Memahami Teks Bahasa Jerman Melalui PAIKEM - Sri Haryati Palallung; Misnawaty Usman; Wahyu Kurniati Asri (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this research is to know about the increase in reading comprehension through PAIKEM of the students of class XI IPA at the SMA PGRI Ge’tengan Tana Toraja. This research is a class action research that consists of two cycles and each cycle consists of two meetings. The subject in this research is the class XI IPA SMA PGRI Ge’tengan student. The data analysis techniques in this research are qualitative and quantitative. Qualitative data were obtained from observations and quantitative data from the results of student evaluations. The results of the student evaluation showed that reading comprehension of German text had increased with an average of 77 points in cycle I and 91 in cycle 2. From this it can be concluded that the use of the PAIKEM of reading comprehension German text by PAIKEM of the students of class XI IPA can increase.